2020
DOI: 10.3389/fpsyt.2019.00978
|View full text |Cite
|
Sign up to set email alerts
|

Bad Things Come to Those Who Do Not Wait: Temporal Discounting Is Associated With Compulsive Overeating, Eating Disorder Psychopathology and Food Addiction

Abstract: The tendency to act on immediate pleasure-driven desires, due to the devaluation of future rewards [a process known as temporal discounting (TD)], has been associated with substance use disorders (SUD) and with conditions characterised by compulsive overeating. The study involved a large inclusive participant sample (i.e., no diagnostic or exclusion criteria were applied). They were recruited/assessed online and we investigated whether TD was related to compulsive overeating and associated problems. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 69 publications
0
15
0
1
Order By: Relevance
“…Decreased modulation of putative executive function regions has also been found in women with obesity during difficult vs. easy trials of a delay discounting task (Stoeckel et al, 2013), suggesting that dysfunctional interactions between executive control and interceptive networks could contribute to excessive food intake (Steward, Menchon, et al, 2017;Syan et al, 2019). This compulsive eating pattern is associated with addictive-like eating behavior in obesity and is often defined using symptoms parallel to those of substance use disorders and behavioral addictions (Kakoschke, Aarts, & Verdejo-Garc ıa, 2019;Kekic et al, 2020). Likewise, addictive behaviors have been robustly associated with steep discounting to delayed reward (Volkow & Baler, 2015), suggesting the presence of overlapping brain systems mediating appetitive and addictive behaviors (Volkow & Baler, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased modulation of putative executive function regions has also been found in women with obesity during difficult vs. easy trials of a delay discounting task (Stoeckel et al, 2013), suggesting that dysfunctional interactions between executive control and interceptive networks could contribute to excessive food intake (Steward, Menchon, et al, 2017;Syan et al, 2019). This compulsive eating pattern is associated with addictive-like eating behavior in obesity and is often defined using symptoms parallel to those of substance use disorders and behavioral addictions (Kakoschke, Aarts, & Verdejo-Garc ıa, 2019;Kekic et al, 2020). Likewise, addictive behaviors have been robustly associated with steep discounting to delayed reward (Volkow & Baler, 2015), suggesting the presence of overlapping brain systems mediating appetitive and addictive behaviors (Volkow & Baler, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers support a framework wherein patients with BED represent a subgroup within a heterogeneous obesity phenotype (Hege et al, 2015;Jim enez-Murcia et al, 2019;Schag, Sch€ onleber, Teufel, Zipfel, & Giel, 2013). In pattern akin to behavioral addictions and substance abuse (Minhas et al, 2021;, studies have also identified an association between higher discount rates and symptomatology in individuals with obesity and BED (Kekic et al, 2020;Manwaring, Green, Myerson, Strube, & Wilfley, 2011). Women with BED and obesity have been found to present steeper discounting rates to food reward, compared to women with obesity without BED (non-BED) (Manwaring et al, 2011) and to monetary rewards, compared to control participants (Bartholdy et al, 2017;Steward, Mestre-Bach, Vintr o-Alcaraz, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another facet of mental damage concerning information entropy is that it might occur due to the unsustainable accumulation of information. In other words, the extended effort to process information overwhelms the neural system and deteriorates into immune and mental problems [72] , [79] .…”
Section: Thermodynamic Considerations Of Brain Activitiesmentioning
confidence: 99%
“…Third, BMI was significantly greater in women with BN relative to HC women. BMI is associated with elevated delay discounting of monetary reward in persons with disordered eating (Kekic et al, 2020). As such, we controlled for BMI in our analyses, yet women with BN still showed decreased delay discounting of food and momentary reward relative to HC women.…”
Section: Limitationsmentioning
confidence: 99%